A Contribution to the Theory of Business Cycles - Foley, D. K. (Quarterly Journal of Economics, 1992)
An economy consisting of identical perfectly competitive firms with real liquidity costs and a one-period production lag has a locally unstable stationary equilibrium with complex eigenvalues for a wide range of parameters. Monetary policy aimed at stabilizing real balances can support nonstationary equilibrium paths that converge to a limit cycle, which has Keynesian features. The First Welfare Theorem does not hold because the price level appears in the production function through liquidity costs, so that production has a positive externality.